P268 IBD and Covid-19 in italy: comparisons between first and second pandemic wave. (21st January 2022) - Bezzio, C; Costa, S; Armuzzi, A; Furfaro, F; Ardizzone, S; Milla, M; Bossa, F; Orlando, A; Caprioli, F A; Castiglione, F; Viganò, C; Ribaldone, D G; et al.
Abstract: Background: Coronavirus disease 2019 (COVID-19), had two pandemic waves in 2020, respectively in April and November. In the general population, the first wave has been characterized by a higher prevalence in Northern Italy and a higher mortality rate compared to the second one. The aim of this study was to compare the characteristics of IBD patients and negative outcomes of COVID-19 (pneumonia, hospitalization, ventilatory support, death) between the two pandemic waves in Italy. Methods: Prospective observational cohort study. Patients with diagnosis of IBD and confirmed SARS-CoV-2 infection were enrolled. Differences between first and second wave were tested for significance using the Student's t test and Fisher's test, as appropriate. A two-tailed p value <0.05 was indicative of statistical significance. Results: We enrolled 937 IBD patients from 47 participating IBD centres across Italy (219 in the first wave, 718 in the second wave). There were no significant differences between the first and the second wave in terms of age (46.3 ± 16.0 vs. 44.1 ± 15.5 years, p=0.06) and gender (female 45.7% vs. 48.2%, p= 0.54). In the first wave, a lower percentage of patients was affected by Crohn's disease (CD): 92 (42.0%) vs. 399 (55.6%) (p<0.001) while no differences were observed for disease clinical activity: 97/219 (44.3%) vs. 280/718 (38.9%) in the first and second wave, respectively (p=0.18). Regarding biologic therapy, the percentage of patients on biologics in the two waves was similar: 119/219 (54.3%) vs. 393/718 (54.7%) (p=0.94), without differences in anti-TNFalpha, anti-integrins and anti-IL12/23 distribution. During the first wave, a significantly higher percentage of patients were from Northern Italy compared to Central-Southern Italy: 171/219 (78.1%) vs. 387/718 (53.9%), respectively (p<0.001). Overall, COVID-19 negative outcomes were significantly higher in the first wave compared to the second one: 110 (50.2%) vs. 95 (13.2%), respectively (p<0.001). Also the single negative outcomes were significantly higher in the first wave: 61/219 (27.8%) vs. 84/718 (11.7%) had pneumonia, 62/219 (28.3%) vs. 76/718 (10.6%) required hospitalization, 26/219 (11.9%) vs. 39/718 (5.4%) required ventilatory support, and 12/219 (5.5%) vs. 13/718 (1.8%) died (Figure 1). Conclusion: IBD patients had higher number of COVID-19 negative outcomes in the first wave than in second wave. In the first wave, a significantly higher percentage of patients were from Northern Italy, but no significant differences in negative outcomes were observed in comparison with those from Central- Southern Italy. Overall, findings in IBD population are coherent with those observed in the general population.